The Mediating Effect of Tourists ' Feedback Information on the Relationship between Interaction and Service Innovation in Tanzania - Busagara, Theresia; Mori, Neema; Jan, Dev (University of Dar es Salaam Library Journal, 2024)
Studies on feedback information and interactions among tourists and tourism services are limited to residents, service providers, and mostly business-to-business. Little remains unknown about the relevance of tourists ' feedback information and interactions to service innovation. This study examined the mediating effect of tourist feedback information in the relationship between tourists ' interactions and service innovation. A survey of 290 Tanzanian tourism firms gathered the scale data that was analysed using Structural Equation Modelling in the Partial Least Square method. Tourist feedback information and tourists ' interactions were found to positively affect service innovation. While tourists ' interactions exhibited a strong positive effect on service innovation, there is a partial mediation of feedback information between the two. These results inform the service industry to capitalize on customer feedback information in enriching new service designs. As a result, practitioners in service firms are at a high point to set strategies to improve interactions as good practices in service innovation. Specifically, the tourism industry actors obtain insights into handling customers and benefiting from their actions and information. Theoretically, the study offers an understanding of interactions as applied in the service dominant logic such that apart from the exchange focus, feedback and interactions can also be considered as information sources for service innovation across firms. These results suggest that tourist interactions and feedback should be treated as key information points for enabling service innovation.